Fabrication and performance of nanostructured ZnO/SnO₂ based humidity sensor / Nor Diyana Md Sin - Md Sin, Nor Diyana (Institute of Graduate Studies, UiTM, 2015)
Humidity sensors were fabricated using zinc oxide/tin oxide (ZnO/SnO₂) composite nanorods and novel structures of ZnO/ SnO2 nanoblock arrays and ZnO/SnO2 composite nanocubes. The ZnO/SnO₂ composite nanorods and ZnO/SnO₂ nanoblock arrays were successfully synthesised using thermal chemical vapour deposition (CVD). The ZnO/SnO₂ composite nanocubes were prepared using a novel sol-gel immersion method. First, ZnO thin films were synthesised to prepare the ZnO/SnO₂ composite nanorods and the ZnO/SnO₂ composite nanocubes. These ZnO thin films acted as template layers, which were deposited using a radio frequency (RF) magnetron sputtering system. To obtain a conductive template layer, parametric studies were conducted by varying the RF power and the temperature of the substrate. This template was optimised using a RF power of 200 watts and a substrate temperature of 500°C to obtain the ZnO template with the highest conductivity of 73.1 S cm-1. The ZnO/SnO₂ composite nanorods were studied by varying different parameters including the ZnO/SnO₂ composition, the type of tin precursor (i.e., dibutyltin diacetate, tin powder and tin chloride pentahydrate), the substrate temperature (between 200 and 600°C) and the oxygen flow rate (5, 10 and 15 sccm). The sensitivity of the humidity sensor and the response and recovery times were studied in each experiment. The experimental results were used to relate the sensor performance to the surface conditions in terms of the dimension of the active layer…